Clinicopathological and molecular features of responders to nivolumab for patients with advanced gastric cancer. Issue 1 (31st January 2019) - Mishima, Saori; Kawazoe, Akihito; Nakamura, Yoshiaki; Sasaki, Akinori; Kotani, Daisuke; Kuboki, Yasutoshi; Bando, Hideaki; Kojima, Takashi; Doi, Toshihiko; Ohtsu, Atsushi; Yoshino, Takayuki; Kuwata, Takeshi; et al.
Abstract : Background: Clinicopathological and molecular features of responders to nivolumab for advanced gastric cancer (AGC) are not well understood. Methods: Patients (pts) with AGC who were treated with nivolumab after two or more chemotherapy regimens in a single institution from September 2017 to May 2018 were enrolled in this study. PD-L1 expression in tumor cells (TC) and mismatch repair (MMR) were analyzed by immunohistochemistry. Epstein-Barr virus (EBV) was detected by in situ hybridization. Cancer genome alterations were evaluated by a next-generation sequencing-based panel. High tumor mutation burden (TMB) was defined as more than 10 mutations/megabase. Results: A total of 80 pts were analyzed in this study. Tumor response was evaluated in 72 pts with measurable lesions and 14 pts (19%) had an objective response. Overall response rate (ORR) was significantly higher in pts with ECOGPS 0 in those with PS 1 or 2, MMR-deficient (MMR-D) in those with MMR-proficient (MMR-P), PD-L1+ in TC in those with PD-L1- in TC and PIK3CA mutation in those with PIK3CA wild-type. ORR was 31% in pts with at least one of the following factors; MMR-D, high TMB, EBV+ and PD-L1+ in TC vs. 0% in those without these factors. Progression-free survival was significantly longer in pts with PS 0 than in those with PS 1 or 2, MMR-D than in those with MMR-P, and PD-L1+ in TC than in those with PD-L1- in TC. Conclusions: Some features were associated with favorable response to nivolumab for AGC. Combining these features might be useful to predict efficacy.